Zinc(II) complexes of 3,10-C-meso-2,5,5,7,9,12,12,14- octamethyl-1,8-diaza-4,11-diazoniacyclotetradecane as its bis(acetate) trihydrate, [LBH2][CH3COO]2.3H2O: Synthesis, Characterization and antimicrobial studies - Biswas, Foni B.; Rabi, Saswata; Barua, Kanak; Roy, Tapashi G.; Palit, Debashis; Dey, Benu K. (European Scientific Journal, ESJ, 2018)
One isomeric ligand, LB among three isomers (LA, LB and LC) of 2,9- C-meso-2,5,5,7,9,12,12,14-octamethyl-1,4,8,11-tetraazacyclotetradecanes, differing in the orientation of methyl groups on the chiral carbon atoms) on interaction with vinyl acetate produces 2,9-C-meso-2,5,5,7,9,12,12,14- octamethyl-1,8-diaza-4,11-diazoniacyclotetradecane as its bis(acetate) trihydrate, [LBH2][OOCCH3]2.3H2O. This ligand salt trihydrate reacts with Zn(CH3COO)2.2H2O to produce square pyramidal monoacetatozinc(II) acetate complex [ZnLB(CH3COO)](CH3COO), which undergoes anion exchange reaction with NaClO4.6H2O to produce monoacetatozinc(II) perchlorate complex, [ZnLB(CH3COO)](ClO4). The complex, [ZnLB(CH3COO)](ClO4) undergoes axial substitution reactions with KSCN, NaNO2 and KNO3 to form the substitution products, [ZnLB(NCS)](NCS), [ZnLB(NO2)](ClO4) and [ZnLB(NO3)](ClO4) respectively where CH3COOis replaced by NCS- , NO3 - and NO2 - . All these complexes have been characterized on the basis of analytical, spectroscopic, conductometric and magnetochemical data. The antifungal and antibacterial activities of these compounds have been studied against some phytopathogenic fungi and bacteria.